PEMANFAATAN BUMDES DALAM MENINGKATKAN TARAF HIDUP MASYARAKAT DESA PESAWAHAN TIRIS KABUPATEN PROBOLINGGO - Adnan Quthny, Abu Yazid; Bukhori, Imam (Lembaga Penerbitan, Penelitian, dan Pengabdian Masyarakat (LP3M) UNZAHLP3M, 2021)
The village is the center of the nation's economic activity. Hence from that implementationdevelopment in stages is the village. The government has begun to prioritize rural development in order to improve and prosper the people. Village development has been regulated in law. The potential of the village is very extraordinary so that it can prosper its citizens, this requires input and reaction from the community, cohesiveness must be built so that all residents benefit. The village is the center of the nation's economic activity. Therefore, the development was carried out in stages, namely the village. The government is currently starting to prioritize village development in order to improve the welfare of residents. This matter has been included in a special law controlling village development. The village has a very good ability for the welfare of the nation, so that this matter needs to be mobilized so that its usefulness can be felt for all residents. The presence of Bumdes illustrates the implementation of Law Number. 6 of 2014 concerning villages, namely what if the community could increase the income of the population by mobilizing the village potential which was decided in a coordination meeting between the community and the village government with the ideas and ideas of the residents. In connection with this, the problem that can be found in this research is how to improve the economy of the population through Bumdes in Pesawahan Village, Tiris District, Probolinggo Regency. This research has the aim of how to improve the economy of the villagers with the existence of bumdes in Pesawahan Village, Tiris District, Probolinggo Regency. This research is a field research which has a descriptive character, which describes some of the findings of information formulated in words. The author takes illustrative information using purposive sampling. Based on the criteria that the authors share, up to 10 illustrations. The equipment the writer needs to get the information is the result of interviews, observations and documentation. The results of this research show how the Bumdes governance process for the economic level of residents is tried through the opening of some business units that are very much needed by residents, namely market management and development, management of household productive business units and other service units. Some units can be used as business opportunities for residents to find new jobs. In conclusion, the results of this research, if the presence of Bumdes can and can be an efficient strategy in developing the capacity of the village to improve a prosperous village. With the presence of Bumdes, we can allocate funds according to the wishes of the villagers.